(untitled) (Web of Teachers: Inderscience Research, 2026)
This exploratory mixed-method study examines how mood (Uzbek kayfiyat) is conceptualized and linguistically encoded in the Baburnama and how Uzbek EFL learners attempt to preserve mood when translating between Uzbek and English. Drawing on a small set of ko‘ngil-based phraseological items and their renderings in three major English translations (Leyden & Erskine, 1826; Beveridge, 1921; Thackston, 1996), the study identifies recurring translation shifts: (1) locus relocation (ko‘ngil/heart to mind), (2) metaphor restructuring (motion/impact to weather imagery or dispositional predication), and (3) explicitation (affective settling to cognitive adequacy). A pilot learner component (N = 20) combined a short questionnaire with an Uzbek-to-English translation task and an English mood-identification task. Learners reported frequent translation practice and strong reliance on imagery and connotation for mood recognition, and none preferred strict literalism when mood conflicted with propositional meaning. Qualitative analysis suggests generally successful preservation of a calm, sensory mood in a descriptive passage, but greater variation in labeling and justifying mood in an English narrative. Pedagogical implications are discussed for mood-focused translation training in the Uzbek EFL context.